Politik hukum internasional / Christian Reus-Smit ; penerjemah Derta Sri Widowatie ; penyunting Irfan M. Zaki. - REUS-SMIT, Christian; Derta Sri Widowatie; Irfan M. Zaki (Nusa Media, 2015)
xvi, 473 hlm. ; 22 cm [3 eks.]